PH neutralization and influence on mechanical strength in self-adhesive resin luting agents - Zorzin, José Ignacio; Petschelt, Anselm; Ebert, Johannes; Lohbauer, Ulrich (Dental Materials, 2012)
Objective: The aim of this study was to evaluate if pH-neutralization behavior of self-adhesive resin cements has an influence on their mechanical properties. Methods: pH-neutralization, water sorption, solubility and flexural strength of G-Cem Automix (GCA), G CEM Capsules (GCC), Maxcem Elite (MCE), RelyX Unicem Clicker (RXC), RelyX Unicem Maxicap (RXM), RelyX Unicem 2 (RX2), and Speed-Cem (SPC) were tested in self-curing mode. Specimen's pH-values were recorded up to 24 h with a pH-electrode. Water sorption (WS) and solubility (SO) were measured. Flexural strength (FS) was evaluated before and after thermocycling (TC) and fracture surfaces analyzed under SEM. Results: RX2 (pH 24 5.89), RXC (pH 24 5.49) and SPC (pH 24 5.42) showed highest 24 h pH-values, followed by GCA (pH 24 5.34). Capsulated products and MCE (pH 24 3.90) reached lower pH-values. GCC (75.78 μg/mm 3) showed the highest WS followed by MX (69.64 μg/mm 3), RXM (64.76 μg/mm 3), GCA (25.86 μg/mm 3) and SPC (30.42 μg/mm 3). Capsulated products RXM (56.58 μg/mm 3) and GCC (30.94 μg/mm 3) presented the highest SO, GCA (4.06 μg/mm 3) and SPC (4.26 μg/mm 3) revealed the lowest. GCA (114.03 MPa) had the highest initial FS followed by SPC (79.81 MPa), RXM (41.61 MPa) the lowest. FS of all materials decreased significantly after TC except for RXC (44.65 MPa) and RX2 (65.92 MPa). FS of GCC (16.47 MPa) and MCE (28.21 MPa) decayed the most. A highly linear correlation was observed between percentage decrease of FS after TC and 24 h pH-values (R 2 = 0.861). Significance: Within the limits of this study pH-neutralization behavior has an influence on mechanical stability. When using self-adhesive resin luting agents, automix-syringe products with improved pH-neutralization behavior should be favored. © 2012 Academy of Dental Materials.
CRIS-Team Scopus Importer:2023-01-23
Keywords: Dental cement; Flexural strength; Luting agent; Mechanical stability; pH; Physical behavior; Self-adhesive; Water solubility; Water sorption